2018
DOI: 10.24127/akuisisi.v14i1.249
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Patronage Buying Motives Terhadap Prinsip Going Concern Pada UMKM

Abstract: This article aims to analyze the influence of patronage buying motives namely of company location, production facility, price, and product quality on going concern principle on UMKM of fried onion in Palu. Respondents in the study were owners or managers of UMKM fried onion industries in Palu, Population 52 based on data from the Industry and Trade Office, but only 40 were active. Data obtained through questionnaires and interviews, processed by SPSS program. Data analysis was done by multiple linear regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
0
6
1
6
Order By: Relevance
“…The results of this study indicate that price affects profitability. Other studies prove that selling prices affect an increase in sales of a company's products (Ginting et al, 2014;Totanan, 2018;Yuliati, 2011). Instead, this study found that the guarantee of fried onion products as local food did not affect profitability.…”
Section: Discussioncontrasting
confidence: 51%
See 4 more Smart Citations
“…The results of this study indicate that price affects profitability. Other studies prove that selling prices affect an increase in sales of a company's products (Ginting et al, 2014;Totanan, 2018;Yuliati, 2011). Instead, this study found that the guarantee of fried onion products as local food did not affect profitability.…”
Section: Discussioncontrasting
confidence: 51%
“…Ghanimata (2012) proves that the location of sales is a variable that most influences the tendency of consumers to buy a product. This is supported by Totanan (2018) that the location of sales influences the going concern principle.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations